2019
DOI: 10.1088/1361-665x/ab3a0c
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive capacitive pressure sensor with elastic metallized sponge

Abstract: This paper presents a novel capacitive pressure sensor that is capable of making highly accurate measurements at low pressure. Different from the method that many researchers have successfully used to improve the sensitivity of capacitive sensors by using a micro-structured dielectric layer (such as the micro-structured PDMS film), this paper creatively used an elastic metallized sponge (nickel-plated polyurethane sponge) as the elastic porous electrode of the capacitive sensor, so that it can detect very low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Similar to micropatterned structures, porous layers have also been recently used to structure the electrode. [ 90 ] Using this method, the capacitance change is dependent on the change in contact area between the porous electrode and the dielectric layer.…”
Section: Capacitive Pressure Sensorsmentioning
confidence: 99%
“…Similar to micropatterned structures, porous layers have also been recently used to structure the electrode. [ 90 ] Using this method, the capacitance change is dependent on the change in contact area between the porous electrode and the dielectric layer.…”
Section: Capacitive Pressure Sensorsmentioning
confidence: 99%
“…The sensors are evaluated in an overview comparison with other existing works. Our sensors have a sensitivity higher than two studies, (0.283 kPa −1 at 5 kPa) [26] and (121 × 10 −4 kPa −1 at 100 kPa) [48], and lower than two studies (0.007 kPa −1 at 5 kPa) [34,49]. Our sensors also have a lower thickness than those studies, as shown in Figure 8.…”
Section: Characterization Of the E-fabric Skinmentioning
confidence: 50%
“…Our sensors also have a lower thickness than those studies, as shown in Figure 8. Due to using the spacer fabric, the sensors also have better breathable properties than the reference samples in two studies [34] (using aluminum foil), and [48] (using silicone layers). The spacer layers by the PET yarns will also be more highly elastic than the silicone.…”
Section: Characterization Of the E-fabric Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 16,17 ] The sensitivity and resolution of some sensors have exceeded that of human fingertip skin. [ 18,19 ] However, the large‐scale use of tactile sensor arrays is still a challenging problem. This is because the number of sensor units will increase significantly with the increase of coverage area, and the computing scale of signal processing will also increase significantly.…”
Section: Introductionmentioning
confidence: 99%